Experience Of Chronic Obstructive Pulmonary Disease (COPD) Patients In Self-Care - Ghifari, M. Ikhsan; Rahmah, R. A. Gabby Novikadarti; Neri, Ervina Lili; Yulanda, Nita Arisanti (Nursing Information Journal, 2025)
Self-care is a crucial aspect of COPD management, as it can improve quality of life. However, many COPD patients still face challenges in self-care due to various factors, one of which is social support. The purpose of this research is to explore in-depth the support and barriers to self-care in COPD patients. This study was a descriptive qualitative research with a phenomenological approach through in-depth interviews. Participants consisted of 6 people from RSUD Dr. Soedarso Pontianak selected by purposive sampling technique. The inclusion criteria were COPD patients diagnosed for approximately six months, able to participate in interviews, with adequate understanding of their condition, and residing in Pontianak. The exclusion criteria were patients with comorbid acute or chronic illnesses, those experiencing COPD exacerbations, or not residing in Pontianak. The research instruments used were a voice recorder (mobile phone), in-depth interview guidelines, and stationery. Data analysis used the Miles & Huberman analysis method. The study produced three main themes, namely the initial experience and process of self-care, support and expectations in self-care and barriers to self-care. This study shows that the experience of COPD patientsn self-care is influenced by supporting and inhibiting factors. Supporting factors include family role support, social environment, quality and expectations of health services that help patients in maintaining health and managing symptoms. Inhibiting factors, such as environmental influences, physical limitations, limitations in medication management and lack of social support and stress that worsen the patient's condition which hinders the patient's self-care process.